From Supramolecular Organic Cages to Porous Covalent Organic Frameworks for Enhancing Iodine Adsorption Capability by Fully Exposed Nitrogen‐Rich Sites - Cheng, Ke; Li, Hailian; Wang, Jia‐Rui; Li, Pei‐Zhou; Zhao, Yanli (Small (Weinheim an der Bergstrasse, Germany), 2023)
In order to overcome the limitations of supramolecular organic cages for their incomplete accessibility of active sites in the solid state and uneasy recyclability in liquid solution, herein a nitrogen‐rich organic cage is rationally linked into framework systems and four isoreticular covalent organic frameworks (COFs), that is, Cage‐TFB‐COF, Cage‐NTBA‐COF, Cage‐TFPB‐COF, and Cage‐TFPT‐COF, are successfully synthesized. Structure determination reveals that they are all high‐quality crystalline materials derived from the eclipsed packing of related isoreticular two‐dimensional frameworks. Since the nitrogen‐rich sites usually have a high affinity toward iodine species, iodine adsorption investigations are carried out and the results show that all of them display an enhancement in iodine adsorption capacities. Especially, Cage‐NTBA‐COF exhibits an iodine adsorption capacity of 304 wt%, 14‐fold higher than the solid sample packed from the cage itself. The strong interactions between the nitrogen‐rich sites and the adsorbed iodine species are revealed by spectral analyses. This work demonstrates that, utilizing the reticular chemistry strategy to extend the close‐packed supramolecular organic cages into crystalline porous framework solids, their inherent properties can be greatly exploited for targeted applications. Linking supramolecular organic cages with triple‐symmetric organic connectors, covalent organic frameworks (COFs) are successfully constructed. Obvious enhancement in iodine uptake up to 14 times higher than that of the solid packed by the cage itself is achieved, demonstrating that extending the close‐packed supramolecular organic cages into crystalline porous frameworks can be employed for targeted applications.